Cómo Lidiar con Abejas Africanas: Una Guía Práctica - Michael K. O'Malley; James D. Ellis; Pablo Herrera; Anita S. Neal (EDIS)
ENY-141S, a 4-page fact sheet by M. K. O’Malley, J. D. Ellis, Pablo Herrera, and A. S. Neal, is the Spanish language version of ENY-141/IN739 What to do about African Honey Bees: A Consumer Guide. It provides information about Africanized honey bees (AHB), which have been labeled "killer" bees, steps people can take to avoid negative interactions, how to handle stings, and bee-proofing basics. Published by the UF Department of Entomology and Nematology, August 2010.